2019
DOI: 10.1016/j.antiviral.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin is an APE1 redox inhibitor and exhibits an antiviral activity against KSHV replication and pathogenesis

Abstract: Curcumin, a polyphenol, is the main bioactive compound in dietary spice turmeric curcuma longa.It possesses anti-inflammatory, anti-oxidant and anti-neoplastic properties and shows potentials in treating or preventing particular diseases such as oxidative and inflammatory conditions, metabolic syndrome, arthritis, anxiety, hyperlipidemia and cancers. The diverse range and potential health beneficial effects has generated enthusiasm leading to intensive investigation into the phytochemical. However, a concern h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
(49 reference statements)
0
29
1
Order By: Relevance
“…However, these effects were all blocked by curcumin, and the results indicated that curcumin increased APE1 expression and activity in cerebral I/R injury. However, an earlier study revealed that curcumin is an inhibitor of the APE1 redox function that affects numerous genes and pathways, which is contrary to the results of the current study (42). These differences may be a result of the different research systems used: The previous study examined a virus system, while the present study investigated SH-SY5Y cells.…”
Section: Discussioncontrasting
confidence: 96%
“…However, these effects were all blocked by curcumin, and the results indicated that curcumin increased APE1 expression and activity in cerebral I/R injury. However, an earlier study revealed that curcumin is an inhibitor of the APE1 redox function that affects numerous genes and pathways, which is contrary to the results of the current study (42). These differences may be a result of the different research systems used: The previous study examined a virus system, while the present study investigated SH-SY5Y cells.…”
Section: Discussioncontrasting
confidence: 96%
“…Replication Human immunodeficiency virus [11] APE1 redox reactions Replication Kaposi's sarcoma-associated herpesvirus [12] Cell lipogenesis Replication Dengue virus [8]…”
Section: Antioxidationmentioning
confidence: 99%
“…Li et al [12] noted while reviewing the genes and pathways impacted by curcumin that there was overlap with pathways controlling the redox reaction of apurinic/apyrimidinic endonuclease 1 (APE1), suggesting curcumin could inhibit APE1 redox reactions. Since Kaposi's sarcoma-associated herpesvirus (KSHV) replication requires the redox function of APE1 [76], the authors investigated whether curcumin could inhibit KSHV replication.…”
Section: Kaposi's Sarcoma-associated Herpesvirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Chen et al, 2013;C¸ıkrıkc¸I et al, 2008;Dhillon et al, 2008;S. C. Gupta et al, 2013;H. Li et al, 2019;Mathew & Hsu, 2018;Narayanan et al, 2012;Prasad & Tyagi, 2015;Si et al, 2007).…”
Section: Introductionmentioning
confidence: 99%